Brain Cell Death Is Reduced With Cooling by 3.5°C to 5°C but Increased With Cooling by 8.5°C in a Piglet Asphyxia Model. Issue 1 (January 2015) - Alonso-Alconada, Daniel; Broad, Kevin D.; Bainbridge, Alan; Chandrasekaran, Manigandan; Faulkner, Stuart D.; Kerenyi, Áron; Hassell, Jane; Rocha-Ferreira, Eridan; Hristova, Mariya; Fleiss, Bobbi; Bennett, Kate; Kelen, Dorottya; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— In infants with moderate to severe neonatal encephalopathy, whole-body cooling at 33°C to 34°C for 72 hours is standard care with a number needed to treat to prevent a adverse outcome of 6 to 7. The precise brain temperature providing optimal neuroprotection is unknown. Methods— After a quantified global cerebral hypoxic-ischemic insult, 28 piglets aged <24 hours were randomized (each group, n=7) to (1) normothermia (38.5°C throughout) or whole-body cooling 2 to 26 hours after insult to (2) 35°C, (3) 33.5°C, or (4) 30°C. At 48 hours after hypoxia-ischemia, delayed cell death (terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick end labeling and cleaved caspase 3) and microglial ramification (ionized calcium-binding adapter molecule 1) were evaluated. Results— At 48 hours after hypoxia-ischemia, substantial cerebral injury was found in the normothermia and 30°C hypothermia groups. However, with 35°C and 33.5°C cooling, a clear reduction in delayed cell death and microglial activation was observed in most brain regions (P<0.05), with no differences between 35°C and 33.5°C cooling groups. A protective pattern was observed, with U-shaped temperature dependence in delayed cell death in periventricular white matter, caudate nucleus, putamen, hippocampus, and thalamus. A microglial activation pattern was also seen, with inverted U-shaped temperature dependence in periventricular white matter, caudate nucleus, internal capsule, and hippocampus (all P<0.05). Conclusions— Cooling to 35°C (an absolute drop of 3.5°C as in therapeutic hypothermia protocols) or to 33.5°C provided protection in most brain regions after a cerebral hypoxic-ischemic insult in the newborn piglet. Although the relatively wide therapeutic range of a 3.5°C to 5°C drop in temperature reassured, overcooling (an 8.5°C drop) was clearly detrimental in some brain regions.